The Sustainable Business Model Development For Smes In Palm Post-Harvest Equipment - Hanik Atus Sangadah; Rahmadini Payla Juarsa (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
Small and medium industries that produce post-harvest tools for oil palm are growing quite rapidly in Riau Province. The business activities carried out by MSMEs need to be continuously developed especially business model. This study uses SWOT analysis to determine business model development strategy. The strategy obtained from the SWOT analysis is then used to develop BMC 2.0 with activities that must be maintained, developed, and created. BMC 1.0 resulted from observations and interviews with business actors. The results of this study are the formulation of BMC 2.0 by applying each strategy resulting from the SWOT analysis which is carried out including creating products that are more diverse and in accordance with SNI standards, actively participating in activities or programs from the Regional Government, producing tools according to requests from consumers, and starting to adopt a recording system digital finance. The results of BMC 2.0 can be used as a reference for MSMEs in developing their business units, namely by implementing a market penetration strategy to obtain broader market or consumer segmentation.